EFEKTIVITAS PENERTIBAN PENAMBANGAN EMAS ILEGAL DI KABUPATEN DHARMASRAYA - Widi Puspa Sari; Adil Mubarak (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2020)
This articles describes the effectiveness of procedure control of ilegal gold mining activities in Dharmasraya distric. Researcher uses the theory according to Tangkilisan about an indicator of the effectiveness. The research method used qualitative descriptive. Informan in this research using purposive sampling technique. In the data collection uses by interview, observation, and documentation technique. The result research explain that the effectiveness the ilegal gold mining control in the Dharmasraya distric has not been implemented opportune and optimally. It shows there are still many problems. Such as there are not clarity of the purpose and strategy, special program, planning, policy are not written and supervision system has been not optimally. This causes the control does not go as expexcted. The causative factors of ilegal gold mining control can include by internal and external factors. Internal factors are lack of human resources, budget, and facilities. While eksternal factors are low of community participation, location far away, and leakage information. That is the reason why the effectiveness of the ilegal gold mining control in the Dharmasraya distric has not gone well.